Innovation for sustainability, an imperative in the global context - Cortez-Angulo, Lilia (Unidad Editorial UPTC, 2021)
Economic, social and environmental conditions in the world are becoming increasingly complex. Global problems, such as the SARS-COV2 pandemic (Hsu et al., 2020), migrations caused by war or poverty (Valle, 2021), as well as climate change resulting from global warming (Houghton, 2005) bring with them economic, environmental, and therefore social deterioration.